2011
DOI: 10.1089/jmf.2010.0191
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anti-Inflammatory Effects of Scoparia dulcis L.

Abstract: Different extracts were obtained from Scoparia dulcis L. (Scrophulariaceae) by successive extraction with hexane, chloroform, and methanol. These extracts exhibited significant antioxidant capacity in various antioxidant models mediated (xantine oxidase and lipoxygenase) or not mediated (2,2-diphenyl-picrylhydrazyl, ferric-reducing antioxidant power, β-carotene bleaching, lipid peroxidation) by enzymes. The antioxidant activity of the extracts was related to their phytochemical composition in terms of polyphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 37 publications
(45 reference statements)
2
20
0
Order By: Relevance
“…This is in accordance with previous studies which pointed non polar extracts to be particularly active on Aspergillus sp, Penicillium sp and Fusarium sp (Mahlo et al, 2010). The strong activity of these non-polar extracts could be related to their high content in terpenes such as β-carotene and lycopene (Coulibaly et al, 2011b) as previously suggested (Gudzic et al, 2002;Cakir et al, 2004).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in accordance with previous studies which pointed non polar extracts to be particularly active on Aspergillus sp, Penicillium sp and Fusarium sp (Mahlo et al, 2010). The strong activity of these non-polar extracts could be related to their high content in terpenes such as β-carotene and lycopene (Coulibaly et al, 2011b) as previously suggested (Gudzic et al, 2002;Cakir et al, 2004).…”
Section: Discussionsupporting
confidence: 92%
“…Some investigations previously evidenced its use to help with the symptoms of several diseases such as arterial hypertension and diabetes mellitus (Satyanarayana, 1969). A number of the medicinal properties of S. dulcis have been previously demonstrated including its anti-diabetic, anti-inflammatory and antioxidant activities in vivo (Pari and Latha, 2005;Adaikpoh et al, 2007), its potent inhibition of DPPH radicals (Babincová and Sourivong, 2001), its antimicrobial activity (Latha et al, 2006) and its impact on lipid peroxidation (Ratnasooriya et al, 2005;Coulibaly et al, 2011b). Furthermore a few phenolic and terpenic compounds have been isolated from S. dulcis including scoparic acid A, scoparic acid B, scopadulin (Hayashi et al, 1991), scopadulcic acid A and B, scopadulciol, scopadulin (Hayashi et al, 1990) and were identified as contributing to the observed medicinal effect of the plant.…”
Section: Introductionmentioning
confidence: 99%
“…Babincová and Sourivong used the DPPH assay to demonstrate strong antioxidant activity of the extract [59]. Coulibaly et al [60] studied the antioxidant property of the hexane, chloroform, and methanol extracts of the plant by the DPPH and FRAP assays. In addition, inhibition of lipid peroxidation was measured by the TBARS assay and inhibition of lipoxygenase and xanthine oxidase by the extracts was determined [60].…”
Section: Other Therapeutic Properties Of S Dulcis Relevant To Diamentioning
confidence: 99%
“…Coulibaly et al [60] studied the antioxidant property of the hexane, chloroform, and methanol extracts of the plant by the DPPH and FRAP assays. In addition, inhibition of lipid peroxidation was measured by the TBARS assay and inhibition of lipoxygenase and xanthine oxidase by the extracts was determined [60]. They found that the chloroform extract exhibited the highest activity and concluded that the phytochemical content being the highest in this extract was the responsible factor for the observation [61, 62].…”
Section: Other Therapeutic Properties Of S Dulcis Relevant To Diamentioning
confidence: 99%
“…These include anti-diabetic properties, anti-hypertensive effects as well as anti-hyperlipidemic and anti-tumour effects. [67] Recently, Coulibaly et al .,[8] showed that the whole S. dulcis plant possessed high antioxidant and anti-inflammatory properties. Furthermore, it has been reported to lower the LDL cholesterol levels in streptozotocin-diabetic rats.…”
Section: Introductionmentioning
confidence: 99%